Calcium hydroxide: study based on scientific evidences - Estrela, Carlos; Holland, Roberto [UNESP] (Faculdade De Odontologia De Bauru - USP, 2003)
The characteristics of calcium hydroxide come from its dissociation into calcium and hydroxyl ions. The action of these ions on tissues and bacteria explains the biological and antimicrobial properties of this substance. Under the conditions of this retrospective of literature, based on scientific evidences, it is possible to state that: 1. Dentin is considered the best pulpal protective, and calcium hydroxide has proved, through numerous studies, its capability of inducing the formation of a mineralized bridge over pulpal tissue. 2. It is necessary, whenever possible, to provide time for calcium hydroxide paste to manifest its potential of action on the microorganisms present in endodontic infections. The maintenance of a high concentration of hydroxyl ions can change bacteria enzymatic activity and promote its inactivation. 3. The site of action of hydroxyl ions of calcium hydroxide includes the enzymes in the cytoplasmic membrane. This medication has a large scope of action, and therefore is effective on a wide range of microorganisms, regardless their metabolic capability. In microbial world, cytoplasmic membranes are similar, irrespective from microorganisms morphological, tinctorial and respiratory characteristics, which means that this medication has a similar effect on aerobic, anaerobic, Gram-positive and Gram-negative bacteria. 4. Calcium hydroxide as temporary dressing used between appointments promotes better results on the periapical healing process than the treatment in one appointment.

As características do hidróxido de cálcio se desenvolvem a partir da dissociação em íons cálcio e hidroxila. A ação desses íons nos tecidos e bactérias explica as características biológicas e antimicrobianas dessa substância. Por meio desta retrospectiva da literatura, baseada em evidências científicas, é possível afirmar que: 1. A dentina é considerada a melhor proteção pulpar, e o hidróxido de cálcio provou, através de numerosos estudos, sua capacidade de induzir a formação de barreira mineralizada sobre o tecido pulpar. 2. É necessário, sempre que possível, dar tempo à pasta de hidróxido de cálcio para manifestar seu potencial de ação sobre os microrganismos presentes nas infecções endodônticas. A manutenção de alta concentração de íons hidroxila pode alterar a atividade enzimática bacteriana e promover sua inativação. 3. O sítio de ação dos íons hidroxila e cálcio incluem as enzimas presentes na membrana citoplasmática. Esta medicação tem um largo espectro de ação, independentemente da capacidade metabólica dos microrganismos. As membranas citoplasmáticas são similares, independentemente das características morfológicas, tintoriais e respiratórias dos microrganismos, o que significa que essa medicação atua de forma similar sobre bactérias aeróbias, anaeróbias, Gram-positivas e Gram-negativas. 4. O hidróxido de cálcio como medicação intracanal, entre sessões, promove melhores resultados no processo de reparação periapical do que o tratamento em sessão única.
Hidróxido de cálcio: estudo baseado em evidências científicas
Keywords: Calcium hydroxide; Dental pulp cavity; Intracanal medication; Mineral trioxide agregate; Portland cement; Hidróxido de cálcio; Polpa dentária; Medicação intracanal; Mineral trioxide agregate; Cimento Portland